2014
DOI: 10.1038/ncb2976
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic roles of EMT-inducing transcription factors

Abstract: The plasticity of cancer cells underlies their capacity to adapt to the selective pressures they encounter during tumour development. Aberrant reactivation of epithelial-mesenchymal transition (EMT), an essential embryonic process, can promote cancer cell plasticity and fuel both tumour initiation and metastatic spread. Here we discuss the roles of EMT-inducing transcription factors in creating a pro-tumorigenic setting characterized by an intrinsic ability to withstand oncogenic insults through the mitigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
716
4
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 882 publications
(773 citation statements)
references
References 135 publications
20
716
4
11
Order By: Relevance
“…The expression of a set of previously described epithelial to mesenchymal transition-related genes 8 was evaluated in both types of endometrial cancer clones and we found that some epithelial to mesenchymal transition genes were expressed more strongly in Ishikawa-TAZ cells, such as SNAI1 (Po0.001), SNAI2 (Po0.001), and HMGA2 (Po0.05: Figure 3a). By contrast, when TAZ expression was silenced in AN3CA cells by either of the shRNAs, we observed a decrease in the expression of the membrane factor SPARC (Po0.001), SNAI1 (Po0.01), ZEB1 (Po0.001), TCF3 (Po0.01), and HMGA2 (Po0.01: Figure 3b).…”
Section: Taz Expression Is Associated With Epithelial To Mesenchymal mentioning
confidence: 90%
See 2 more Smart Citations
“…The expression of a set of previously described epithelial to mesenchymal transition-related genes 8 was evaluated in both types of endometrial cancer clones and we found that some epithelial to mesenchymal transition genes were expressed more strongly in Ishikawa-TAZ cells, such as SNAI1 (Po0.001), SNAI2 (Po0.001), and HMGA2 (Po0.05: Figure 3a). By contrast, when TAZ expression was silenced in AN3CA cells by either of the shRNAs, we observed a decrease in the expression of the membrane factor SPARC (Po0.001), SNAI1 (Po0.01), ZEB1 (Po0.001), TCF3 (Po0.01), and HMGA2 (Po0.01: Figure 3b).…”
Section: Taz Expression Is Associated With Epithelial To Mesenchymal mentioning
confidence: 90%
“…7 The epithelial to mesenchymal transition is coordinated by a network of transcription factors that regulate the expression of proteins involved in cell polarity, cell-cell contacts, cytoskeletal structure, and extracellular matrix degradation. 8 The loss of E-cadherin expression is a crucial event in epithelial to mesenchymal transition and indeed, transcription factors associated to epithelial to mesenchymal transition can be grouped according to their ability to directly or indirectly repress E-cadherin. 9 Among the direct repressors, we can find zinc finger proteins like SNAIL1, SNAIL2, ZEB1 (TCF8), ZEB2 (SIP1), and the bHLH factor E47 (TCF3) or KLF8.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5c). Since EMT is a critical process in cell migration and invasion [23,24], we further analyzed the role of GKN1 and RhoA in the expression of EMT-related proteins. In MKN1 gastric cancer cells, ectopic GKN1 expression, or silencing of RhoA, increased E-cadherin expression, and decreased the expression of RhoA, Snail, Slug, and vimentin (Fig.…”
Section: The Effects Of Gkn1 and Rhoa On Gastric Cancer Cell Migratiomentioning
confidence: 99%
“…16,17 Additional genes including WNT5, NOTCH1, CAV1 and CCND1 have also been observed in several models of EMT and metastasis. 4,[18][19][20][21] These observations indicate that H2A.X loss leads to the activation of EMT program in breast cells. As many of the movement-associated genes observed in MCF10A cells were also found to regulate EMT, migration and invasion in human colon cancer cell line HCT116, 12 our data suggest the existence of H2A.X-driven EMT signature shared by breast and colon cancer cells.…”
Section: Differential Gene Expression Analysismentioning
confidence: 74%